Assistance in the management of the Al-Amin Islamic Majelis Ta’lim program to improve the Fiqh literacy of the people of Kediri City - Syajarul Imna Mohd Amin; Luthfi Abdul Manaf; Muhammad Zen Masruri; Yusuf Fauzi; Achris Ahsanudtaqwin (LP2M Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2026)
Purpose: The objective of this study is Assistance in the management of the Al-Amin Islamic Majelis Ta’lim program to improve the Fiqh literacy of the people of Kediri City, and to explore the background of these activities and the factors that support and hinder their implementation. Method: The community service method in this research adopts the Asset-Based Community Development (ABCD) approach, a model of community empowerment that emphasizes the use of community assets and potential to improve their quality of life. Practical Applications: his management mentoring activity for the Majelis Ta’lim (Islamic study group) has successfully had a positive impact on community life, faith, and ways of thinking. The religious teachings provided enhance understanding of religious principles, Islamic law, and community moral values; this, in turn, helps strengthen faith and belief. Conclusion: The ABCD approach has proven effective in driving behavioral change and sustainably enhancing community capacity, starting with asset mapping and potential management, implementation, and evaluation. Majelis Ta’lim activities have been organized through the development of an organizational structure where management roles are assigned according to each individual's expertise and through the development of activity plans through deliberations involving various stakeholders.